2022
DOI: 10.1101/2022.09.22.509014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Grazers affect the composition of dissolved storage glycans and thereby bacterioplankton composition during a biphasic North Sea spring algae bloom

Abstract: Blooms of marine microalgae play a pivotal role in global carbon cycling. Such blooms entail successive blooms of specialized clades of planktonic bacteria that remineralize algal biomass. We investigated the bacterioplankton response to a bloom in the German Bight in spring 2020. Metagenome sequencing at 30 time-points allowed reconstruction of 251 metagenome-assembled genomes (MAGs), 245 representing as yet uncultured species, while corresponding metatranscriptome sequencing highlighted 50 particularly activ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 70 publications
0
29
0
Order By: Relevance
“…The ability to process αand β-linked glucans via external hydrolysis and/or selfish uptake is likely widespread among heterotrophic bacteria, due to the abundance of these polysaccharides in the ocean. Along these lines, a recent study has demonstrated that αand βglucan processing enzymes are widely and preferentially expressed by a broad phylogenetic range of bacteria during a spring phytoplankton bloom (Sidhu et al, 2023). Their target substrates are commonly available: annual oceanic production of laminarin has been estimated to be on the order of 5-15 billion metric tons (Alderkamp et al, 2007;Becker et al, 2020), and external hydrolysis of laminarin has been detected at almost every station and depth in the ocean surveyed to date (e.g., Arnosti et al, 2011;Balmonte et al, 2021).…”
Section: Substrate-specific Changes Demonstrate a Nuanced Response Of...mentioning
confidence: 99%
“…The ability to process αand β-linked glucans via external hydrolysis and/or selfish uptake is likely widespread among heterotrophic bacteria, due to the abundance of these polysaccharides in the ocean. Along these lines, a recent study has demonstrated that αand βglucan processing enzymes are widely and preferentially expressed by a broad phylogenetic range of bacteria during a spring phytoplankton bloom (Sidhu et al, 2023). Their target substrates are commonly available: annual oceanic production of laminarin has been estimated to be on the order of 5-15 billion metric tons (Alderkamp et al, 2007;Becker et al, 2020), and external hydrolysis of laminarin has been detected at almost every station and depth in the ocean surveyed to date (e.g., Arnosti et al, 2011;Balmonte et al, 2021).…”
Section: Substrate-specific Changes Demonstrate a Nuanced Response Of...mentioning
confidence: 99%
“…During the spring of 2020, surface seawater samples were collected from the 'Kabeltonne' long-term ecological research station off the North Sea of Helgoland (54°11.3' N, 7°54.0' E) as described previously [13,14]. Surface water samples were collected on 2020-03-10, 2020-04-14, 2020-04-30, and 2020-05-06.…”
Section: Sampling and Sequencingmentioning
confidence: 99%
“…Metagenomes and MAGs data are available from the European Nucleotide Archive (ENA) project PRJEB52999 [14].…”
Section: Data Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its abundance, water solubility and simple structure, marine bacteria often prefer laminarin as a substrate over less soluble and more complex polysaccharides (4,5). Polysaccharide utilization loci (PULs) dedicated to laminarin breakdown are thus both widely distributed (6,7) and are highly expressed (4,(8)(9)(10) in marine bacteria that thrive during phytoplankton blooms. PULs are distinct genetic loci that encode proteins to sense, digest and transport sugars.…”
Section: Introductionmentioning
confidence: 99%